2007
DOI: 10.1016/j.bbabio.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Phycobilin/chlorophyll excitation equilibration upon carotenoid-induced non-photochemical fluorescence quenching in phycobilisomes of the cyanobacterium Synechocystis sp. PCC 6803

Abstract: To determine the mechanism of carotenoid-sensitized non-photochemical quenching in cyanobacteria, the kinetics of blue-light-induced quenching and fluorescence spectra were studied in the wild type and mutants of Synechocystis sp. PCC 6803 grown with or without iron. The blue-light-induced quenching was observed in the wild type as well as in mutants lacking PS II or IsiA confirming that neither IsiA nor PS II is required for carotenoid-triggered fluorescence quenching. Both fluorescence at 660 nm (originating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 33 publications
6
46
0
Order By: Relevance
“…Samples were excited at 435 nm, and emission spectra were adjusted for same signal at the fluorescein peak at 522 nm. The fluorescein component from emission spectra was subtracted and normalized to the 721 nm emission band (41).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were excited at 435 nm, and emission spectra were adjusted for same signal at the fluorescein peak at 522 nm. The fluorescein component from emission spectra was subtracted and normalized to the 721 nm emission band (41).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the mechanism of thermal energy dissipation in cyanobacteria, which plays a key role in global carbon cycling, remained elusive. Only within the last few years has a photoprotective mechanism associated with the soluble phycobilisome antenna of PSII in cyanobacteria been demonstrated (8)(9)(10)(11)(12)(13)(14). A specific soluble carotenoid protein, the orange carotenoid protein (OCP), plays an essential role in this process (9,10).…”
mentioning
confidence: 99%
“…In previous studies it has been proposed that IsiA is involved in the generation of the large blue light-induced NPQ observed in Synechocystis under iron starvation (Cadoret et al, 2004). But later, it was shown that this iron-stress induced NPQ was OCP-but not IsiA-dependent (Rakhimberdieva et al, 2007;Wilson et al, 2007).…”
Section: T Elongatus and Synechocystismentioning
confidence: 99%
“…The function of the OCP in the photoprotective PB-related thermal dissipating mechanism has been examined so far only in Synechocystis cells (Wilson et al, 2006;Rakhimberdieva et al, 2007;Wilson et al, 2007). It is, however, not known if this important mechanism is widespread among cyanobacteria, or not.…”
Section: Presence Of the Ocp Gene In Diferent Cyanobacteriamentioning
confidence: 99%
See 1 more Smart Citation